Voltage Sag and Swell Mitigation Using Dynamic Voltage Restorer in Grid Connected PV System - Win Sandar; Han Phyo Wai (AI Society & STMIK Indonesia, 2025)
Three transformers and twelve feeders make up the Mandalay Zone (2) substation in Pyigyitagon Township. The industrial load feeder is load feeder B, which has a 45 MVA and 132/11 KV capacity. Other feeders include A, B, C, D, E, F and the Awarat/55 feeders. A number of faults in the industrial load feeder B may result in different voltage sags. The load feeder B can meet voltage swell when the sudden load decrease, fault clearance, capacitor starting, unbalanced loads, lightning strikes, grid overvoltage, etc., appear. A dynamic voltage restorer (DVR) is connected in series between the source and protected load feeder B in order to compensate for voltage sag and swell in the suggested system. The DVR's design is taken into account for a 0.5 sag in voltage. The compensation voltage is produced by the DVR's voltage source inverter and sent into the grid via the injection transformer after the DVR first detects voltage sag and swell. To return it to normal, the DVR absorbs excess voltage during a swell or injects the missing voltage during a sag. The synchronous reference frame theory is used for the control of DVR. The load voltage is approximately 9.02 kV after all feeders and faults have been compensated for, and the rated values have been restored. For every feeder and all faults, the THD% on the voltage of the faulted phase A is less than 5%. After compensation, the THD% for the remaining phases is approximately 5%. Likewise, the THD% on current is less than 5% for every phase and all faults. The DVR can only make up for for grid side voltage sag brought on by different faults. During faults, the solar plant's AC power output dropped.